Alkali-activation of fly ash and cement kiln dust mixtures for stabilization of demolition aggregates. (20th October 2018) - Mohammadinia, Alireza; Arulrajah, Arul; D'Amico, Angelo; Horpibulsuk, Suksun
Highlights: A combination of CKD and FA was evaluated as an alternative low carbone binder. CKD complents FA and creates better cementatious products. A CKD:FA ratio of 50:50 found to be the optimum binder content. Abstract: Utilization of industrial by-products such as cement kiln dust (CKD) and fly ash (FA) for increasing the strength and stiffness of demolition waste aggregates can be an optimal and sustainable solution for reducing the carbon footprint of the construction activities. Furthermore, this approach of incorporating waste materials as construction materials will also reduce the rapid depletion rate of natural resources. This research presents an optimization, by means of evaluating combinations of CKD + FA blends to utilize the rich source of calcium and silica and alumina in these by-products. The impact of sample preparation method is investigated. The use of alkaline solutions facilitates the progression of activation process in room temperature. Recycled Concrete Aggregate (RCA), Crushed Brick (CB) and Reclaimed Asphalt Pavement (RAP) are three major components of the demolition waste stream and were used as the parent materials in this research for assessment of the efficiency of stabilization process. The durability of the stabilized materials under repeated loading was investigated. In addition, the resilient modulus of the stabilized materials were compared with the empirical models to assess the impact of confining stress and deviatoric stress on the moduli of the mixtures. The optimum ratio of FA:CKD of 50:50 showed the highest performance. The research indicates that alkali-activation of 15%CKD and 15%FA blended with C&D aggregates provided the optimum blend for the usage of these wastes as construction materials.